Thermal stability of laser-clad tool steel with fine tungsten carbide particle addition - Fazliana, Fauzun; Syarifah Nur Aqida, Syed Ahmad; Abdul Fattah, Mohd Tahir; Izwan, Ismail (Springer US, 2025)
Thermal stability of laser-modified surfaces is crucial for hot working conditions. Refined grain structure from the rapid solidification can only withstand a limited temperature range before the grain structure merges from grain boundary movement. Although the superior hardness properties are achievable through laser cladding, laser-clad surfaces are prone to cracking due to a mismatch in thermal expansion coefficient and coarse, hard particle size addition. Thus, this paper presents the thermal stability of laser-clad H13 tool steel with fine tungsten carbide (WC) particles (1-5 µm) addition to obstruct grain boundary movement and retain the refined grain structure. Controlled parameters for WC particle settlement onto H13 steel are laser power, pulse repetition frequency (PRF) and scanning speed. A thermal fatigue test was conducted on the clad surface for 1000-5000 cycles. The thermally worn clad surfaces were characterised for subsurface hardness properties, surface morphology and topography. The findings suggest the addition of WC particles during H13 steel surface melting increases the hardness properties to 2389 HV. Although the total volume of eroded surface and crack propagation responds evidently to the fatigue cycles, the refined grain structure is primarily intact, thus retaining the surface properties under high working temperatures. The WC particles observed amongst dendrite structure after 5000 cycles of fatigue test signify thermal stability at temperatures above 600°C. The thermal model anticipated higher stress distribution on the WC particles clad surface relative to the H13 steel substrate. These findings indicate fine particles’ significance in strengthening grain structure for designing a prolonged dies surface life cycle.